Horticultural therapy for stress reduction: A systematic review and meta-analysis - Lu, Shan; Liu, Jianjiao; Xu, Meijing; Xu, Feng (Frontiers in Psychology, 2023)
Horticultural therapy has been increasingly accepted as a non-pharmacological stress reduction treatment. Previous studies have demonstrated its therapeutic effects, with the effect varying according to the populations, settings, and interventions of horticultural therapy. This study aimed to provide a comprehensive review of the current literature regarding the effectiveness of horticultural therapy in reducing stress. We selected databases including PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure, and VIP Data as our data source, and the original search was completed in January 2023. Our results showed significantly increased effects of horticultural therapy on psychological indicators compared to a control group, but an insignificant effect on physiology indicators. The result of the subgroup analysis demonstrated that the stress-reducing effects of horticultural therapy were related to the characteristics of the population and indoor and virtual areas were the most effective setting for horticultural therapy. At the same time, a total duration of 100-500 minutes provided better effects of stress reduction. We also developed a theoretical framework based on a “Participants-Settings-Interventions” structure for horticulture therapy in terms of its stress-reduction effects, to provide a reference for future horticultural therapy activities.